Solid Organ Rejection following SARS-CoV-2 Vaccination or COVID-19 Infection: A Systematic Review and Meta-Analysis - Alhumaid, Saad; Rabaan, Ali A; Dhama, Kuldeep; Yong, Shin Jie *; Nainu, Firzan; Hajissa, Khalid; Al Dossary, Nourah; Alajmi, Khulood Khaled; Al Saggar, Afaf E.; AlHarbi, Fahad Abdullah; Aswany, Mohammed Buhays; Alsyhayee, Abdullah Abdulaziz; et al. (MDPI, 2022)
Background: Solid organ rejection post-SARS-CoV-2 vaccination or COVID-19 infection is extremely rare but can occur. T-cell recognition of antigen is the primary and central event that leads to the cascade of events that result in rejection of a transplanted organ. Objectives: To describe the results of a systematic review for solid organ rejections following SARS-CoV-2 vaccination or COVID-19 infection. Methods: For this systematic review and meta-analysis, we searched Proquest, Medline, Embase, Pubmed, CINAHL, Wiley online library, Scopus and Nature through the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines for studies on the incidence of solid organ rejection post-SARS-CoV-2 vaccination or COVID-19 infection, published from 1 December 2019 to 31 May 2022, with English language restriction. Results: One hundred thirty-six cases from fifty-two articles were included in the qualitative synthesis of this systematic review (56 solid organs rejected post-SARS-CoV-2 vaccination and 40 solid organs rejected following COVID-19 infection). Cornea rejection (44 cases) was the most frequent organ observed post-SARS-CoV-2 vaccination and following COVID-19 infection, followed by kidney rejection (36 cases), liver rejection (12 cases), lung rejection (2 cases), heart rejection (1 case) and pancreas rejection (1 case). The median or mean patient age ranged from 23 to 94 years across the studies. The majority of the patients were male (n = 51, 53.1%) and were of White (Caucasian) (n = 51, 53.7%) and Hispanic (n = 15, 15.8%) ethnicity. A total of fifty-six solid organ rejections were reported post-SARS-CoV-2 vaccination [Pfizer-BioNTech (n = 31), Moderna (n = 14), Oxford Uni-AstraZeneca (n = 10) and Sinovac-CoronaVac (n = 1)]. The median time from SARS-CoV-2 vaccination to organ rejection was 13.5 h (IQR, 3.2–17.2), while the median time from COVID-19 infection to organ rejection was 14 h (IQR, 5–21). Most patients were easily treated without any serious complications, recovered and did not require long-term allograft rejection therapy [graft success (n = 70, 85.4%), graft failure (n = 12, 14.6%), survived (n = 90, 95.7%) and died (n = 4, 4.3%)]. Conclusion: The reported evidence of solid organ rejections post-SARS-CoV-2 vaccination or COIVD-19 infection should not discourage vaccination against this worldwide pandemic. The number of reported cases is relatively small in relation to the hundreds of millions of vaccinations that have occurred, and the protective benefits offered by SARS-CoV-2 vaccination far outweigh the risks.